The anthropogenic impact on snow chemistry at Colle Gnifetti, Swiss Alps - Wagenbach, D.; Münnich, K.O.; Schotterer, U.; Oeschger, H. (Annals of Glaciology, 1988)
By chemical analysis of the upper 40 m of a 124 m ice core from a high-altitude Alpine glacier (Colle Gnifetti, Swiss Alps; 4450 m a.s.l.), records of mineral dust, pH, melt-water conductivity, nitrate and sulfate are obtained. The characteristics of the drilling site are discussed, as derived from glacio-meteorological and chemical analysis. As a consequence of high snow-erosion rates (usually during the winter months), annual snow accumulation is dominated by summer precipitation. Clean-air conditions prevail even during summer; however, they are frequently interrupted by polluted air masses or by air masses which are heavily loaded with desert dust. Absolutely dated reference horizons for Saharan dust, together with the position of the broad nuclear-weapon tritium peak, provide the time-scale for the following statements: (1) Since at least the turn of the century the background melt-water conductivity has been rising steadily, as has the mean snow acidity. The trend of increasing background conductivity at Colle Gnifetti (1.9μS/cm around the beginning of this century, and at present 3.4 μS/cm) is found to be comparable with the records of mean melt-water conductivity reported from ice cores from the Canadian High Arctic. (2) Sulfate and nitrate concentrations are higher by a factor of 4–5 than they were at the beginning of the century. This is to be compared with the two- to three-fold rise in the concentrations in south Greenland during about the same time span.